Potential Anti-Mycobacterium tuberculosis Activity of Plant Secondary Metabolites: Insight with Molecular Docking Interactions - Manu Kumar; Sandeep Kumar Singh; Prem Pratap Singh; Vipin Kumar Singh; Avinash Chandra Rai; Akhileshwar Kumar Srivastava; Livleen Shukla; Mahipal Singh Kesawat; Atul Kumar Jaiswal; Sang-Min Chung; Ajay Kumar (Antioxidants, 2021)
Tuberculosis (TB) is a recurrent and progressive disease, with high mortality rates worldwide. The drug-resistance phenomenon of Mycobacterium tuberculosis is a major obstruction of allelopathy treatment. An adverse side effect of allelopathic treatment is that it causes serious health complications. The search for suitable alternatives of conventional regimens is needed, i.e., by considering medicinal plant secondary metabolites to explore anti-TB drugs, targeting the action site of M. tuberculosis. Nowadays, plant-derived secondary metabolites are widely known for their beneficial uses, i.e., as antioxidants, antimicrobial agents, and in the treatment of a wide range of chronic human diseases (e.g., tuberculosis), and are known to “thwart” disease virulence. In this regard, in silico studies can reveal the inhibitory potential of plant-derived secondary metabolites against Mycobacterium at the very early stage of infection. Computational approaches based on different algorithms could play a significant role in screening plant metabolites against disease virulence of tuberculosis for drug designing.